Improvements in exercise performance: effects of carbohydrate feedings and diet - Neufer, P. D.; Costill, D. L.; Flynn, M. G.; Kirwan, J. P.; Mitchell, J. B.; Houmard, J. (Journal of Applied Physiology, 1987)
In an effort to determine the effects of carbohydrate (CHO) feedings immediately before exercise in both the fasted and fed state, 10 well-trained male cyclists [maximum O2 consumption (VO2 max), 4.35 +/- 0.11 l/min)] performed 45 min of cycling at 77% VO2 max followed by a 15-min performance ride on an isokinetic cycle ergometer. After a 12-h fast, subjects ingested 45 g of liquid carbohydrate (LCHO), solid carbohydrate confectionery bar (SCHO), or placebo (P) 5 min before exercise. An additional trial was performed in which a high-CHO meal (200 g) taken 4 h before exercise was combined with a confectionery bar feeding (M + SCHO) immediately before the activity. At 10 min of exercise, serum glucose values were elevated by 18 and 24% during SCHO and LCHO, respectively, compared with P. At 0 and 45 min no significant differences were observed in muscle glycogen concentration or total use between the four trials. Total work produced during the final 15 min of exercise was significantly greater (P less than 0.05) during M + SCHO (194,735 +/- 9,448 N X m), compared with all other trials and significantly greater (P less than 0.05) during LCHO and SCHO (175,204 +/- 11,780 and 176,013 +/- 10,465 N X m, respectively) than trial P (159,143 +/- 11,407 N X m). These results suggest that, under conditions when CHO stores are less than optimal, exercise performance is enhanced with the ingestion of 45 g of CHO 5 min before 1 h of intense cycling.